Miskonsepsi Pemahaman Materi Bangun Datar dengan Penerapan Teori Polya di PGMI 3 UIN Sumatera Utara - Yunita Azhari; Rora Rizki Wandini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Misconceptions are misunderstandings in understanding mathematical concepts. Mathematics misconceptions are still experienced by many students in tertiary institutions. The aim of this research was to analyze errors in understanding questions about Flat Figures by applying Polya Theory. Polya's theory consists of 4 steps, namely understanding the problem, planning, implementing and assessing. This type of assessment is descriptive qualitative research. This research was conducted on PGMI 3 students by taking 6 students as research subjects. The supporting instruments in this research are a 2-item ability test about Flat Figures, observation and interviews. The results of this research indicate that there are misconceptions that occur in understanding Flat Figure problems by applying Polya Theory, namely that out of 6 students there are 4 people who experience misconceptions. Factors that cause students to experience misconceptions include internal and external factors. Internal factors include students not writing down notations/symbols, and students' lack of understanding of the steps of polya theory. Meanwhile, the external factor is that students have too many outside activities so they don't focus on working on plane shape questions given by the teacher and there is a lack of motivation for students to work on plane shape questions.